Countryside, landscape and heritage in (new) historical Geography: Some considerations in the current geographical tendencies - Angel Paniagua (AIMS Geosciences, 2021)
The geographical histories are a field of study of notable heterogeneity and influenced by other geographical sub-disciplines such as cultural geography, rural geography or social geography. The countryside, the past landscape and the heritage are key themes in the new historical geography through the micro or small place histories. Research into key cases of studies allows for the elaboration of broader interpretive frameworks. Current methodological trends are highly influenced by the general orientations of cultural and rural geography, with broad relevance to qualitative methodologies on selected cases. This allows for a mundane geographical history from below that breaks with the general interpretive schemes of academics experts. This has notably influenced the research sources used in the new historical geography with the emergence of oral histories as a source of research for the preparation of contrasted biographies of places and the articulated use of new and old or classic sources —mainly archives—of information. The development of an environmental history in the context of the new historical geography is due to the relevance of the hybrid relationships between nature-culture-society that currently characterize modern geographical research.